Grób skrzynkowy kultury pomorskiej z Odrów, gm. Czersk, stan. 3 w Borach Tucholskich - Górska-Grabarczyk, Beata (Acta Universitatis Lodziensis. Folia Archaeologica, 1994)
Test excavations of the cemetery of the Pomeranian culture on site 3 at Odry revealed in 1991 an undisturbed cist grave with 3 urns containing bones of an adult and of two children. One of the urns with child’s remains has yielded an amulet of animal tooth. The grave has been assigned to the Middle La Тѐпе period.